Identification of early salt stress responsive proteins in seedling roots of upland cotton (Gossypium hirsutum L.) employing iTRAQ-based proteomic technique - Li, Wu; Zhao, Fu’an; Fang, Weiping; Xie, Deyi; Hou, Jianan; Yang, Xiaojie; Zhao, Yuanming; Tang, Zhongjie; Nie, Lihong; Lv, Shuping (Frontiers in Plant Science, 2015)
Soil salinity is a major abiotic stress that limits plant growth and agricultural productivity. Upland cotton (Gossypium hirsutum L.) is highly tolerant to salinity; however, large-scale proteomic data of cotton in response to salt-stress are still scanty. Here, an iTRAQ-based proteomic technique was employed to identify the early differentially expressed proteins (DEPs) from salt-treated cotton roots. 77 up-regulated and 52 down-regulated proteins were identified. The majority of the proteins have functions related to carbohydrate and energy metabolism, transcription related, protein metabolism, cell wall and cytoskeleton metabolism, membrane and transport, signal transduction, as well as stress and defense. It is worth emphasizing that some novel salt-responsive proteins were identified, which involved in cell cytoskeleton metabolism（ARP2 and FLAs）, membrane transport（TIPs and PIPs）, signal transduction（LRR-RLKs）and stress responses(TLP, USP, DIR，desiccation-related protein PCC13-62). High positive correlation was evaluated between the abundance of some altered proteins (SOD, POD, GST, MDAR and MDH) and their enzyme activity. The results demonstrate the iTRAQ-based proteomic technique is reliable for identifying and quantifying a large number of cotton root proteins. qRT-PCR was used to study the gene expression levels of five above-mentioned proteins, four patterns are consistent with those of induced protein. These results showed that cotton’s proteome to NaCl stress is complex, and that the comparative protein profiles of roots under salinity vs control improve the understanding of the molecular mechanisms involved in the tolerance of plants to salt stress. It provides a good starting point for further functional elucidation of these DEPs using genetic and/or other approaches, and thereby candidate genes for genetic engineering to improve crop salt tolerance.